Targeted gene replacement at the URA3 locus of the basidiomycetous yeast Pseudozyma antarctica and its transformation using lithium acetate treatment. Issue 12 (21st September 2017) - Yarimizu, Tohru; Shimoi, Hitoshi; Sameshima‐Yamashita, Yuka; Morita, Tomotake; Koike, Hideaki; Watanabe, Takashi; Kitamoto, Hiroko
Abstract: The basidiomycetous yeast Pseudozyma antarctica is a remarkable producer of industrially valuable enzymes and extracellular glycolipids. In this study, we developed a method for targeted gene replacement in P. antarctica . In addition, transformation conditions were optimized using lithium acetate, single‐stranded carrier DNA and polyethylene glycol (lithium acetate treatment), generally used for ascomycetous yeast transformation. In the rice‐derived P. antarctica strain GB‐4(0), Pa URA3, a homologue of the Saccharomyces cerevisiae orotidine‐5′‐phosphate decarboxylase gene ( URA3 ), was selected as the target locus. A disruption cassette was constructed by linking the nouseothricine resistance gene ( natMX4 ) to homologous DNA fragments of Pa URA3, then electroporated into the strain GB‐4(0). We obtained strain PGB015 as one of the Pa URA3 disruptants (Pa ura3 Δ:: natMX4 ). Then the PCR‐amplified Pa URA3 fragment was introduced into PGB015, and growth of transformant colonies but not background colonies was observed on selective media lacking uracil. The complementation of uracil‐auxotrophy in PGB015 by introduction of Pa URA3 was also performed using lithium acetate treatment, which resulted in a transformation efficiency of 985 CFU/6.8 μg DNA and a gene‐targeting ratio of two among 30 transformants. Copyright © 2017 John Wiley & Sons, Ltd.